2006
DOI: 10.1007/s00213-006-0563-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with MDMA from P11–20 disrupts spatial learning and path integration learning in adolescent rats but only spatial learning in older rats

Abstract: Rationale-Previous studies in rats showed that postnatal day (P)11-20 exposure to ±3,4-methylenedioxymetham-phetamine (MDMA, ecstasy) causes learning and memory deficits in adulthood. The emergence and permanence of these learning deficits are currently unknown.Objective-This study was designed to investigate learning and memory deficits in adolescent (P30 or P40) and older (P180 or P360) rats exposed to MDMA from P11-20.Materials and methods-Within each litter half the animals were exposed to MDMA (20 mg/ kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 34 publications
9
53
1
Order By: Relevance
“…Among other things, adolescence in humans is associated with high levels of sensation-seeking behavior and a desire for novelty (Adriani & Laviola, 2004). However, in addition to the reported learning, memory, impulsivity, and cognitive impairments described here and elsewhere (e.g., Compton et al, 2011;Green et al, 2003;Skelton et al, 2006Skelton et al, , 2009) the use of these drugs appears to carry a number of inherent risks. For example, among the reported long-term consequences associated with the use of MDMA are nonmemorial (e.g., Parkinson's Disease; Morton, 2005) deficits.…”
Section: Discussionmentioning
confidence: 68%
“…Among other things, adolescence in humans is associated with high levels of sensation-seeking behavior and a desire for novelty (Adriani & Laviola, 2004). However, in addition to the reported learning, memory, impulsivity, and cognitive impairments described here and elsewhere (e.g., Compton et al, 2011;Green et al, 2003;Skelton et al, 2006Skelton et al, , 2009) the use of these drugs appears to carry a number of inherent risks. For example, among the reported long-term consequences associated with the use of MDMA are nonmemorial (e.g., Parkinson's Disease; Morton, 2005) deficits.…”
Section: Discussionmentioning
confidence: 68%
“…During probe trials, MDMA treatment groups showed decreased time in the target quadrant for animals beginning testing on P30, but not in animals that began testing at P40, whereas P180 and P360 tested animals showed deficits depending on the phase of the MWM procedure. MDMA-treated animals tested on P180 showed decreased time in the target quadrant during the acquisition and reversal phases of probe trial testing compared with saline-treated animals, whereas at P360 MDMAtreated animals showed deficits during the acquisition and reduced platform probe trials (Skelton et al, 2006). It seems that the function of the 5-HT receptors during memory consolidation changes as animals age: downregulation is seen in younger animals, whereas upregulation is observed in aged animals (Meneses and Perez-Garcia, 2007).…”
Section: Behaviormentioning
confidence: 92%
“…It has been shown that MDMA administration to neonatal rats decreases the rate of weight gain (Broening et al, 1995(Broening et al, , 2001Koprich et al, 2003a;Williams et al, 2003;Meyer et al, 2004;Vorhees et al, 2004;Skelton et al, 2006). This anorectic effect of MDMA continues several weeks after administration of the drug is discontinued; however, weights are similar by adulthood (Broening et al, 2001;Williams et al, 2003;Vorhees et al, 2004;Skelton et al, 2006). In adults it has been shown that MDMA causes a hyperthermic effect when ambient temperatures are over approximately 21°C.…”
Section: Effects Of Neonatal Exposure To Mdma In Animals General Charmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have associated heavy or chronic ecstasy use to persistent cognitive deficits in humans (Morgan 1999;Bhattachary and Powell 2001;Dafters 2006;Quednow et al 2006;Zakzanis and Campbell 2006;Kalechstein et al 2007). Experiments in animals have shown learning and memory alterations in rats (Sprague et al 2003;Able et al 2006;Skelton et al 2006), monkeys (Taffe et al 2001;Frederick and Paule 1997), and mice Rosecrans and Glennon 1987) using a variety of behavioural paradigms. However, pinpointing the underlying mechanism related to these deficits has been difficult, primarily due to the varying profiles of MDMA effects in different species (see Easton and Marsden 2006 for review).…”
Section: Introductionmentioning
confidence: 99%